Distribution of Strongest Aftershock Magnitudes in Mining-Induced Seismicity - Motorin, Alexander; Baranov, Sergey (Frontiers in Earth Science, 2022)
The paper considers the distribution of magnitudes of the strongest aftershocks - depending on the time after the main shock - that occur during the extraction of minerals in tectonically loaded rock massifs. The study is based on the data of long-term seismological observations at the apatite-nepheline deposits of the Khibiny Massif located in the Kola Peninsula. The article demonstrates that the distribution of the difference between the magnitudes of the strongest aftershock and the main shock is described by the dynamic Båth law, previously obtained by the authors during the study of the regularities of aftershock processes of tectonic earthquakes.